New records of soldier flies from Iran with a current checklist and taxonomic notes to some species (Diptera: Stratiomyidae) - Jentzsch, Matthias; Liebig, Wolf-Harald (Zootaxa, 2021)
Soldier fly records of Iran belonging to six species are presented, which includes the first record of Odontomyia annulata (Meigen, 1822) and another record of Adoxomyia cinerascens (Loew, 1873). Odontomyia annulata shows some morphological differences from the description found in the literature. With the addition of O. annulata, the Iranian soldier fly fauna comprises now 48 species. The eastern border of the known range of this species extended to the eastern Black Sea coast and the north-western Caucasus region. Now it has been shifted about 1200 km to the east.